ANALYSIS OF SLANG LANGUAGE IN SONG LYRIC “DAMN I LOVE YOU” BY AGNES MONICA - Rini Moraida Siringoringo; Marlin Steffi Marpaung (Jurnal Scientia, 2022)
Slang is considered as very informal words or phrases. The purpose of this study was to determine the meaning of the slang and to find out the type of the slang in the song lyrics “Damn I Love You”by Agnes Monica. This study discusses the analysis of slang in Agnes Monica's song lyrics. This research is a descriptive qualitative design. The data classified based on the word formation process according to Yule's (2010) theory. Methods and focus on content analysis are used in analysing the data. The analysis starts from October 2021 to November 2021. The results of this study shows that the slang words in Agnes Monica's song consist of several word formations, there are seventeen types of slang word formation in this song. Tthere are three types of slang identified based on the findings from the song clipping, 7 blending, and Coinage. Based on the result, the blending process is the most common process found in Agnes Monica song.